2016
DOI: 10.1111/cyt.12342
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐observer reproducibility of endometrial cytology by the Osaki Study Group method: utilising the Becton Dickinson SurePathliquid‐based cytology

Abstract: In this study, it seemed that the use of the OSG method as the new diagnostic criteria for SP-LBC preparation, may be a valid method to improve the precision (reproducibility) of endometrial cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 14 publications
0
24
0
2
Order By: Relevance
“…Recently, two excellent reporting systems with high reproducibility was reported. We adopted the NTEMC system which Norimatsu proposed . Furthermore, Yanoh et al indicated that the NTEMC system might represent a reported format corresponding to the pathological results of endometrial lesions .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two excellent reporting systems with high reproducibility was reported. We adopted the NTEMC system which Norimatsu proposed . Furthermore, Yanoh et al indicated that the NTEMC system might represent a reported format corresponding to the pathological results of endometrial lesions .…”
Section: Discussionmentioning
confidence: 99%
“…The latest study on endometrial cytologic samples was performed in 2016 by Norimatsu et al, including 244 cases processed with a LBC technique (SurePath™) and assessed by two academic and three non academic cytopathologists in a review round. Both interobserver and intraobserver agreement improved between the two rounds.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we analyzed and defined specimen adequacy, proposing criteria relatively comparable to those proposed previously by the Japanese group. 30,33 We believe that, further interaction between involved scientific teams may lead to the refinement of diagnostic criteria, thus increasing the performance of the classification system. Subsequently, we determined the cytomorphological criteria for each proposed diagnostic category.…”
Section: Discussionmentioning
confidence: 99%
“…In the diagnostic category "without evidence of hyperplasia or malignancy" all cases of normal endometrium were included as well as those cases related to hormonedisordered endometrium along with the anovulatory cycle and stromal breakdown. 33 Determination of diagnostic criteria for categories assigned as: "without evidence of hyperplasia or malignancy" and "malignant" has been Diagnostic Cytopathology DOI 10.1002/dc briefly described in this study, because they are already bibliographically analyzed [18][19][20] and clearly established. However, we focused on the morphology of these lesions in ThinPrepV R -based preparations.…”
Section: Discussionmentioning
confidence: 99%